Fast and neat – Determination of biochemical quality parameters in cocoa using near infrared spectroscopy. (15th August 2015) - Krähmer, Andrea; Engel, Annika; Kadow, Daniel; Ali, Naailah; Umaharan, Pathmanathan; Kroh, Lothar W.; Schulz, Hartwig
Highlights: NIRS was used to determine biochemical quality parameters of cocoa. Comprehensive analysis of cocoa metabolic profiles is achievable by NIRS. Phenolic substances, fermentation time and pH value are reliably predicted with R 2  > 0.92. Organic acids, moisture and N -value could be quantified with R 2  > 0.87. Estimation of cocoa quality by NIRS based prediction of flavor precursors. Abstract: The qualitative heterogeneity and increasing consumption of cocoa products require fast and efficient methods for quality assessment of fermented cocoa with regard to fermentation quality and flavor potential. To date, quality control is achieved by visual inspection (e.g., "cut test") and sensory testing. Chromatographic methods for quantification of flavor relevant substances are limited in their applicability in standard quality control due to laborious isolation and purification steps. Therefore, the aim of this study was the development of a near infrared spectroscopic (NIRS) method for routine analytical prediction of biochemical quality parameters. Different compound classes like phenolic substances ( R 2  = 0.93) or organic acids ( R 2  = 0.88) as well as individual substances like epicatechin ( R 2  = 0.93) or lactic acid ( R 2  = 0.87) could be precisely determined just as fermentation time ( R 2  = 0.92) and pH value ( R 2  = 0.94) presenting NIRS as fast and reliable alternative in routine quality assessment.